Digital disparities and vulnerability : mobile phone use, information behaviour, and disaster preparedness in Southeast Asia - Lai, Chih-Hui (2019)
This paper proposes an ecological view to investigate how disparities in mobile technology use reflect vulnerabilities in communities vis‐à‐vis disaster preparedness. Data (n=1,603) were collected through a multi‐country survey conducted equally in rural and urban areas of Indonesia, Myanmar, Philippines, and Vietnam, where mobile technology has become a dominant and ubiquitous communication and information medium. The findings show that smartphone users' routinised use of mobile technology and their risk perception are significantly associated with disaster preparedness behaviour indirectly through disaster‐related information sharing. In addition to disaster‐specific social support, smartphone users' disaster‐related information repertoires are another strong influencing factor. In contrast, non‐smartphone users are likely to rely solely on receipt of disaster‐specific social support as the motivator of disaster preparedness. The results also reveal demographic and rural–urban differences in disaster information behaviour and preparedness. Given the increasing shift from basic mobile phone models to smartphones, the theoretical and policy‐oriented implications of digital disparities and vulnerability are discussed.